Impact of regional economic development on the spatiotemporal changes of coastlines: a case study of Ningbo-Taizhou-Wenzhou region - Huang, Qiyu; Li, Yifan; Ai, Shunyi; Chen, Yuxin; Liu, Yongchao (Frontiers in Earth Science, 2024)
Coastal areas are densely populated, economically developed, and form complex social-ecological systems. Any regional changes within these areas have profound consequences for their socio-economic development and ecological environments. Based on multi-source remote sensing image data, a detailed analysis of the coastline of the Ningbo-Taizhou-Wenzhou region (Yong-Tai-Wen region) from 1980 to 2020 was conducted, and the spatiotemporal changes of the coastline were analyzed. Regression analysis was employed to investigate the correlation between the coastline length and various factors, including the degree of industrialization, GDP, urban land, and arable land. The results show that: (1) From 1980 to 2020, the overall length of the coastline in the Yong-Tai-Wen region exhibited a decreasing trend, accompanied by a continual increase in the degree of artificial coastline. Consequently, the coastline became increasingly fragmented and tortuous. Notably, the intensity of coastline change fluctuated significantly, peaking in 2010. (2) At the regional scale, there is a strong negative correlation between the length of the coastline in the Yong-Tai-Wen region and GDP and land use, whereas the correlation with cultivated land area remains relatively low. Conversely, the proportion of human-made coastlines demonstrates a strong positive correlation with GDP and urban land use but a significant negative correlation with cultivated land area. (3) At the city scale, the length of the coastline in Ningbo shows a significant negative correlation with GDP while exhibiting a certain correlation with urban land use. Similarly, the coastline length in Taizhou also displays a strong negative association with both GDP and urban land use. In contrast, the correlation patterns observed in Wenzhou are opposite to those in Taizhou. Notably, the correlation between the length of the coastline and cultivated land area remains relatively weak across all three cities. Additionally, the proportion of artificial coastlines in Ningbo and Taizhou aligns with the overall trend in the Yong-Tai-Wen region. Specifically, the proportion of artificial coastlines in Wenzhou exhibits a positive correlation with GDP and urban land use and a negative correlation with cultivated land area.